Seasonal changes in lumbar multifidus muscle in university rugby players - Roy, A.; Rivaz, H.; Rizk, A.; Frenette, S.; Boily, M.; Fortin, M. (Medicine & Science in Sports & Exercise, 2021)
Purpose Although smaller lumbar multifidus muscle (LMM) was reported to be a strong predictor of lower limb injury (LLI) in Australian Football League players, LMM morphology has not been investigated in rugby athletes. This study examined seasonal changes in LMM in rugby players and whether LMM characteristics were associated with low back pain (LBP) and LLI.